High-strength aluminum alloy material for photovoltaic panel assembly and preparation method of high-strength aluminum alloy material
By using rare earth-enhanced aluminum alloy materials in photovoltaic panel components, the problem of insufficient strength of existing aluminum alloys is solved, the strength and hardness of the material are improved, the service life is extended and maintenance costs are reduced.
Patent Information
- Application Number
- CN202411462525.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
The existing 6005 and 6063 aluminum alloys are insufficient in strength and hardness in photovoltaic panel components, resulting in frequent wear and tear during use in the field, increasing maintenance costs and labor intensity.
Using rare earth elements such as Sm, Eu, Yb as reinforcement, combined with Si, Mg, Cu, Mn and other elements, high-strength aluminum alloy materials are prepared through melting, refining, casting, extrusion molding and anodizing treatment to ensure moldability and corrosion resistance while improving the strength and hardness of the material.
It significantly improves the strength and hardness of photovoltaic panel assembly materials, extends service life, reduces maintenance costs and labor intensity, and improves the toughness and fatigue resistance of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy materials and photovoltaic panels, and in particular to a high-strength aluminum alloy material for a photovoltaic panel assembly and a preparation method thereof. Background Art
[0002] As my country's energy problem becomes increasingly tense, many regions are currently using solar photovoltaic panels to generate electricity. Photovoltaic power generation is a technology that uses the photovoltaic effect of the semiconductor interface to directly convert light energy into electrical energy. Using solar power to generate electricity has the effect of energy saving and environmental protection, and can effectively alleviate my country's energy shortage problem.
[0003] The construction and installation of solar photovoltaic panels require a large number of components, including frames, purlins, locks, brackets, etc. At present, these components generally use aluminum alloys, which are characterized by light weight and high strength. The main grades are 6005 and 6063. They have good formability, excellent anodizing performance, and excellent corrosion resistance. However, their strength and hardness are not high, and their resistance to load disturbances imposed by the environment during use is not strong enough. They often need to be replaced due to severe wear during use. Now many solar photovoltaic panels are installed in wild areas. Frequent replacement of solar photovoltaic panel parts requires high maintenance costs, which also increases the labor intensity of staff accordingly. Therefore, a high-strength aluminum alloy material for photovoltaic panel components is needed, which has the same formability, anodizing and corrosion resistance as 6005 and 6063 aluminum alloys, but has higher strength and hardness than 6005 and 6063 aluminum alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength aluminum alloy material for photovoltaic panel components and a preparation method thereof, so as to solve the technical problem that the strength and hardness of the existing 6005 and 6063 aluminum alloys are relatively low. The present invention uses rare earth elements as a reinforcing agent, and while having the same formability, anodizing properties and corrosion resistance as 6005 and 6063 aluminum alloys, it has higher strength and hardness, increases the service life of photovoltaic panels and structural parts, ensures the reliable operation of solar photovoltaic panels, and reduces maintenance costs and labor intensity.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.09-0.9%, Ti: 0.009-0.16%, Mg: 0.3-1.3%, Yb: 0.02-0.7%, Mn: 0.5-1.3%, Cu: 0.08-1.3%, Ag: 0.04-0.4%, B: 0.001-0.04%, Sm: 0.02-0.7%, Eu: 0.02-0.7%, Ni: 0.02-0.4%, Fe≤0.4%, other unavoidable single impurity elements≤0.04%, the total amount of impurity elements≤0.16%, and the balance is aluminum.
[0007] Furthermore, the aluminum alloy material for the photovoltaic panel frame and purlin includes the following components in mass percentage: Si: 0.39-0.9%, Cu: 0.39-1.1%, Mg: 0.39-1.1%, Mn: 0.59-1.1%, Ni: 0.04-0.21%, Ag: 0.02-0.21%, Ti: 0.01-0.13%, B: 0.001-0.026%, Sm: 0.02-0.41%, Eu: 0.02-0.41%, Yb: 0.02-0.41%, Fe≤0.31%, other unavoidable single impurity elements≤0.031%, the total amount of impurity elements≤0.151%, and the balance is aluminum.
[0008] The present invention also provides a method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly, wherein the aluminum alloy material for a photovoltaic panel frame and a purlin is prepared by subjecting aluminum ingots, electrolytic copper, magnesium ingots, aluminum-manganese master alloys, aluminum-nickel master alloys, aluminum-silver master alloys, aluminum-titanium-boron master alloys, aluminum-samarium master alloys, aluminum-europium master alloys, and aluminum-ytterbium master alloys to the steps of melting, refining, casting, extrusion molding, and heat treatment.
[0009] The present invention also provides a method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly, which specifically comprises the following steps:
[0010] Step (1), according to the composition of the high-strength aluminum alloy material for photovoltaic panel components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum-manganese master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy raw materials are configured and weighed;
[0011] Step (2), after placing the first batch of furnace materials: electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy in a smelting furnace, heating the smelting furnace to melt and carry out the first stage of heat preservation smelting, after the furnace materials are melted and reach the expected temperature, mechanical stirring is carried out, and the temperature of the smelting furnace is maintained during stirring; after the first batch of furnace materials are completely melted and stirred evenly, the second batch of furnace materials: aluminum ytterbium master alloy, aluminum samarium master alloy, aluminum europium master alloy, aluminum silver master alloy are added to the smelting furnace, after the furnace materials are completely melted, mechanical stirring is carried out, during stirring, the temperature of the smelting furnace is maintained and the second stage of heat preservation smelting is carried out; after the second batch of furnace materials are completely melted and stirred evenly, magnesium ingot is added, after the magnesium ingot is melted, mechanical stirring is maintained to make the melt uniform, during which the temperature of the smelting furnace is maintained and the third stage of heat preservation smelting is carried out; after stirring evenly, a small amount is taken out from the high-temperature aluminum alloy liquid for chemical composition analysis, if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0012] Step (3), refining the aluminum alloy melt in the smelting furnace, then removing the slag produced in the smelting furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, it does not need to be processed and enters the next process; if the composition deviates, the composition is adjusted, and then sampling and analyzing again, and secondary refining and slag removal are performed, until all elements reach the expected index before entering the next process;
[0013] Step (4), after the refining is completed, the melt is allowed to stand for a period of time, and the melt is kept at a certain temperature before the aluminum alloy liquid is released from the bottom of the furnace for casting, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the aluminum alloy liquid is subjected to double-stage filtration treatment and then enters the casting mold for semi-continuous casting to obtain a round rod-shaped ingot;
[0014] Step (5), placing the round rod ingot in a heating furnace for heating and heat preservation for a certain period of time, then performing a homogenization treatment, then taking the ingot out of the heating furnace and cutting a certain length, and the remaining ingot is again placed in the heating furnace for heat preservation, and the cut ingot is placed in an extruder, and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and after being extruded from the extruder, it is cooled to room temperature by strong wind, and then the cooled profile is straightened and cut into the required length;
[0015] Step (6), placing the profile obtained in step (5) into an aging furnace for artificial aging treatment, taking it out of the furnace after the heat preservation is completed, cooling it to room temperature, and performing an anodizing treatment on it to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0016] Furthermore, in step (1), the contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.4-10.6%, and the ratio of the addition amounts of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is (1-4):(2-7):(1-4).
[0017] Furthermore, in step (2), the first stage heat preservation and melting temperature is 730-830°C, the second stage heat preservation and melting temperature is 720-790°C, and the third stage heat preservation and melting temperature is 670-750°C.
[0018] Furthermore, in step (3), the refining temperature is 670-750° C., the refining time is 40-100 minutes, and the refining gas is 99.99% high-purity argon.
[0019] Furthermore, in step (4), the casting temperature is 650-740°C; the Ti content in the alloy after the addition of the aluminum-titanium-boron master alloy is 0.01-0.06%; the first stage of the two-stage filtration uses a 55-65 mesh ceramic filter plate, and the second stage uses a 75-85 mesh ceramic filter plate; the crystallizer descent speed is 35-245 mm / min.
[0020] Furthermore, in step (5), the homogenization temperature is 440-610° C., the homogenization time is ≥4.5 hours, the extrusion speed is 1-13 m / min, and the cooling method is a combination of strong air cooling and spray cooling.
[0021] Furthermore, in step (6), the artificial aging temperature is 140 to 230° C., and the insulation time is 2 to 13 hours.
[0022] According to the addition amount of alloying elements, purpose, etc., it can be divided into the following categories:
[0023] (1) Main alloying elements. The main alloying elements include Si, Mg, Cu, and Mn. These four elements are added in high amounts in the alloy and are the source of the main properties of the alloy. On the one hand, Si and Mg elements have the effect of solid solution strengthening. On the other hand, they can also form nano-scale β' phase precipitates during artificial aging, producing precipitation strengthening. The Mn element mainly provides the effect of solid solution strengthening. In addition, it can also change the morphology of the Fe-rich phase and improve the plasticity of the alloy material. The Cu element is similar to Si and Mg elements. On the one hand, it has a solid solution strengthening effect. On the other hand, it can also form θ' or Q' phase precipitates during artificial aging, producing precipitation strengthening.
[0024] (2) Transition metal elements. These elements include Ni, Ag, and Ti. Ni can form Al with Al. 3The intermediate phase of Ni is formed by crystallization during the casting solidification process. It is refined and broken through homogenization and extrusion processing, and is evenly distributed in the alloy, hindering the slip of dislocations and the occurrence of dynamic recrystallization. The Ag element can precipitate with Si, Mg, and Cu elements during artificial aging to form a π' phase, producing a precipitation strengthening effect. The Ti element is added to the alloy liquid flow trough through an aluminum-titanium-boron intermediate alloy, and it interacts with Al and B elements to show the effect of refining grains.
[0025] (3) Rare earth elements. Sm, Eu, and Yb are rare earth elements, which can form Al and Al in aluminum alloys. 3 Sm、Al 3 Eu、Al 3 If all three exist at the same time, they will intermix to form a complex intermediate phase of Al3 (Smx, Euy, Ybz), where x, Euy, and z simultaneously satisfy the conditions of x+y+z=1, x≤1, y≤1, and z≤1. On the one hand, these intermediate phases containing rare earth elements crystallize and precipitate during the casting process, resulting in a grain refinement effect; on the other hand, these intermediate phases precipitate and precipitate during the homogenization process, resulting in precipitation strengthening and recrystallization inhibition effects, thereby improving the mechanical properties of the alloy material; on the third hand, rare earth elements can react with trace amounts of H elements in the alloy to form hydrides, converting free H elements into combined states, reducing the risk of H elements agglomerating to form hydrogen and causing internal pores.
[0026] The present invention has the following beneficial effects due to the adoption of the above technical solution:
[0027] 1. The present invention utilizes rare earth elements samarium (Sm), europium (Eu), and ytterbium (Yb), and optimizes the ratio between the three, giving full play to the special physical and metallurgical properties of rare earth elements in aluminum alloys to enhance the strength and plasticity of aluminum alloy materials, thereby improving the toughness, fatigue resistance and other indicators of the materials.
[0028] 2. The present invention utilizes the effect of Ti, B, Ni and rare earth elements in refining the grains of the aluminum alloy, further reducing the grain size of the cast aluminum alloy, and providing good conditions for the alloy material to obtain good performance.
[0029] 3. The present invention utilizes the solid solution strengthening effect produced by the main alloy elements Si, Mg, Cu, and Mn and a series of precipitation phases formed between them and the trace element Ag to produce a strengthening effect and improve the comprehensive performance of the alloy material. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, preferred embodiments are given below to further describe the present invention in detail. However, it should be noted that many details listed in the specification are only for the purpose of enabling the reader to have a thorough understanding of one or more aspects of the present invention, and these aspects of the present invention can be implemented even without these specific details.
[0031] Example 1
[0032] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.64%, Cu: 0.72%, Mg: 0.83%, Mn: 0.69%, Ni: 0.10%, Ag: 0.09%, Ti: 0.04%, B: 0.008%, Sm: 0.09%, Eu: 0.162%, Yb: 0.09%, Fe: 0.12%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum; wherein the mass fraction ratio of Sm, Eu and Yb is 2.5:4.5:2.5.
[0033] The preparation method thereof comprises the following steps:
[0034] Step (1), according to the aluminum alloy material components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum manganese master alloy, aluminum titanium boron master alloy, aluminum samarium master alloy, aluminum nickel master alloy, aluminum silver master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy raw materials are configured and weighed;
[0035] Step (2), after electrolytic copper, aluminum ingot, aluminum nickel master alloy, and aluminum manganese master alloy are placed in a smelting furnace as the first batch of raw materials, the temperature is raised to 770-810°C to melt the charge, and the charge is kept at 785°C and mechanically stirred; the first batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to 730-780°C, a second batch of raw materials such as aluminum silver master alloy, aluminum samarium master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy are added, and the charge is kept at 760°C, and mechanical stirring is maintained during the period; the second batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to 680-740°C, a magnesium ingot is added, and the charge is kept at 720°C, and mechanical stirring is maintained during the period; after stirring evenly, a small amount of the high-temperature aluminum alloy liquid is taken out for chemical composition analysis, and if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0036] Step (3), refining the aluminum alloy melt in the smelting furnace, maintaining the refining temperature in the range of 700-730°C, using 99.99% high-purity argon gas, refining for 60 minutes, then removing the slag produced in the furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, then proceeding to the next process without processing; if the composition deviates, then adjust the composition and sample and analyze again, and perform secondary refining and slag removal until all elements reach the expected index before proceeding to the next process;
[0037] Step (4), after the refining is completed, the melt is allowed to stand for a period of time, and after the melt is kept at a certain temperature, the aluminum alloy liquid is released from the bottom of the furnace for casting, the casting temperature is 689°C, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the amount of aluminum-titanium-boron intermediate alloy added is based on the Ti element content reaching 0.04%. The aluminum alloy liquid is filtered through a double-stage filtration process of 60 mesh and 80 mesh and then enters the casting mold for semi-continuous casting, and the crystallizer descends four degrees at 124 mm / min, and then a round rod-shaped ingot with a diameter of 150 mm is obtained;
[0038] Step (5), placing the round rod ingot into a heating furnace, heating it and keeping it at 545° C. for 6 hours for homogenization treatment, then taking the ingot out of the heating furnace and cutting it to a certain length, and the remaining ingot is again placed in the heating furnace for insulation, and the cut ingot is placed in an extruder and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and the profile extrusion speed is controlled at 6 meters / minute. After the profile is extruded from the extruder outlet, it is immediately subjected to strong wind cooling and spray cooling, and then the profile is straightened and cut into the required length;
[0039] Step (6), placing the profile obtained in step (5) into an aging furnace for artificial aging treatment, wherein the artificial aging temperature is controlled within the range of 160 to 175° C., and the insulation time is controlled within 8 hours. After the insulation is completed, the profile is taken out of the furnace and cooled to room temperature, and anodized to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0040] Example 2
[0041] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.75%, Cu: 1.03%, Mg: 1.06%, Mn: 0.84%, Ni: 0.15%, Ag: 0.21%, Ti: 0.10%, B: 0.02%, Sm: 0.13%, Eu: 0.34%, Yb: 0.17%, Fe: 0.10%, other inevitable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum; wherein the mass fraction ratio of Sm, Eu and Yb is 1.5:4.0:2.0.
[0042] The preparation method thereof comprises the following steps:
[0043] Step (1), according to the alloy material components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum manganese master alloy, aluminum titanium boron master alloy, aluminum samarium master alloy, aluminum nickel master alloy, aluminum silver master alloy, aluminum europium master alloy, aluminum ytterbium master alloy raw materials are configured and weighed;
[0044] Step (2), electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy as the first batch of raw materials are loaded into a melting furnace, heated to 780-830°C to melt the charge, and kept warm at 790°C and mechanically stirred; the first batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 730-770°C, a second batch of raw materials such as aluminum silver master alloy, aluminum samarium master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy are added, and the temperature is kept at 750°C, and mechanical stirring is maintained during the period; the second batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 670-730°C, a magnesium ingot is added, and the temperature is kept at 720°C, and mechanical stirring is maintained during the period; after stirring evenly, a small amount is taken out from the high-temperature aluminum alloy liquid for chemical composition analysis, if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0045] Step (3), refining the aluminum alloy melt in the smelting furnace, maintaining the refining temperature in the range of 700-730°C, using 99.99% high-purity argon gas, refining for 70 minutes, then removing the slag produced in the furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, then proceeding to the next process without processing; if the composition deviates, then adjusting the composition, sampling and analyzing again, and performing secondary refining and slag removal until all elements reach the expected index before proceeding to the next process;
[0046] Step (4), after the refining is completed, the melt is allowed to stand for a period of time while maintaining a certain temperature, and then the aluminum alloy liquid is released from the bottom of the furnace for casting, the casting temperature is 705°C, and when the aluminum alloy liquid enters the flow channel, aluminum titanium boron intermediate alloy wire is added thereto for grain refinement treatment, and the amount of aluminum titanium boron intermediate alloy added is based on the Ti element content reaching 0.10%. After the aluminum alloy liquid is subjected to a double-stage filtration treatment of 60 mesh and 80 mesh, it enters the casting mold for semi-continuous casting, and the crystallizer descends four degrees at 116 mm / min, and then a round rod-shaped ingot with a diameter of 178 mm is obtained;
[0047] Step (5), placing the round rod ingot into a heating furnace, heating it and keeping it at 555° C. for 5 hours for homogenization treatment, then taking the ingot out of the heating furnace and cutting it into a certain length, and the remaining ingot is again placed in the heating furnace for insulation, and the cut ingot is placed in an extruder and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and the profile extrusion speed is controlled at 4 meters / minute. After the profile is extruded from the extruder outlet, it is immediately subjected to strong wind cooling and spray cooling, and then the profile is straightened and cut into the required length;
[0048] Step (6), placing the extruded profile into an aging furnace for artificial aging treatment, wherein the artificial aging temperature is controlled within the range of 170 to 185° C., and the insulation time is controlled within 6 hours. After the insulation is completed, the profile is taken out of the furnace and cooled to room temperature, and anodized to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0049] Example 3
[0050] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.54%, Cu: 0.62%, Mg: 0.76%, Mn: 0.98%, Ni: 0.16%, Ag: 0.17%, Ti: 0.08%, B: 0.01%, Sm: 0.17%, Eu: 0.23%, Yb: 0.12%, Fe: 0.10%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum; wherein the mass fraction ratio of Sm, Eu and Yb is 2.8:4.6:2.4.
[0051] The preparation method thereof comprises the following steps:
[0052] Step (1), according to the alloy material components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum manganese master alloy, aluminum titanium boron master alloy, aluminum samarium master alloy, aluminum nickel master alloy, aluminum silver master alloy, aluminum europium master alloy, aluminum ytterbium master alloy raw materials are configured and weighed;
[0053] Step (2), electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy as the first batch of raw materials are loaded into a melting furnace, heated to 740-790 ° C to melt the charge, and kept warm at 760 ° C and mechanically stirred; the first batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to 720-770 ° C, a second batch of raw materials such as aluminum silver master alloy, aluminum samarium master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy are added, and the temperature is kept at 740 ° C, and mechanical stirring is maintained during the period; the second batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to 670-730 ° C, a magnesium ingot is added, and the temperature is kept at 730 ° C, and mechanical stirring is maintained during the period; after stirring evenly, a small amount of chemical composition analysis is taken out from the high-temperature aluminum alloy liquid, and if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0054] Step (3), refining the aluminum alloy melt in the smelting furnace, maintaining the refining temperature in the range of 700-740°C, using 99.99% high-purity argon gas, refining for 60 minutes, then removing the slag produced in the furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, then proceeding to the next process without processing; if the composition deviates, then adjusting the composition, sampling and analyzing again, and performing secondary refining and slag removal until all elements reach the expected index before proceeding to the next process;
[0055] Step (4), after the refining is completed, the melt is allowed to stand for a period of time while maintaining a certain temperature, and then the aluminum alloy liquid is released from the bottom of the furnace for casting, the casting temperature is 712°C, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the amount of aluminum-titanium-boron intermediate alloy added is based on the Ti element content reaching 0.08%. After the aluminum alloy liquid is subjected to a double-stage filtration treatment of 60 mesh and 80 mesh, it enters the casting mold for semi-continuous casting, and the crystallizer descends four degrees at 154 mm / min, and then a round rod-shaped ingot with a diameter of 150 mm is obtained;
[0056] Step (5), placing the round rod ingot into a heating furnace, heating and keeping it at 560° C. for 5 hours for homogenization treatment, then taking the ingot out of the heating furnace and cutting a certain length, and the remaining ingot is again placed in the heating furnace for insulation, and the cut ingot is placed in an extruder and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and the profile extrusion speed is controlled at 6 meters / minute. After the profile is extruded from the extruder outlet, it is immediately subjected to strong wind cooling and spray cooling, and then the profile is straightened and cut into the required length;
[0057] Step (6), placing the extruded profile into an aging furnace for artificial aging treatment, wherein the artificial aging temperature is controlled within the range of 170 to 195° C., and the insulation time is controlled within 3 hours. After the insulation is completed, the profile is taken out of the furnace and cooled to room temperature, and anodized to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0058] Example 4
[0059] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.85%, Cu: 0.54%, Mg: 0.64%, Mn: 0.78%, Ni: 0.13%, Ag: 0.10%, Ti: 0.06%, B: 0.015%, Sm: 0.10%, Eu: 0.20%, Yb: 0.15%, Fe: 0.18%, other inevitable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum; wherein the mass fraction ratio of Sm, Eu and Yb is 2.0:4.2:2.3.
[0060] The preparation method thereof comprises the following steps:
[0061] Step (1), according to the alloy material components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum manganese master alloy, aluminum titanium boron master alloy, aluminum samarium master alloy, aluminum nickel master alloy, aluminum silver master alloy, aluminum europium master alloy, aluminum ytterbium master alloy raw materials are configured and weighed;
[0062] Step (2), electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy as the first batch of raw materials are loaded into a melting furnace, heated to 750-785°C to melt the charge, and kept warm at 760°C and mechanically stirred; the first batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 725-765°C, a second batch of raw materials such as aluminum silver master alloy, aluminum samarium master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy are added, and the temperature is kept at 740°C, and mechanical stirring is maintained during the period; the second batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 675-725°C, a magnesium ingot is added, and the temperature is kept at 730°C, and mechanical stirring is maintained during the period; after stirring evenly, a small amount is taken out from the high-temperature aluminum alloy liquid for chemical composition analysis, if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0063] Step (3), refining the aluminum alloy melt in the smelting furnace, maintaining the refining temperature in the range of 710-735°C, using 99.99% high-purity argon gas, refining for 60 minutes, then removing the slag produced in the furnace, sampling and analyzing again after the refining, and if the composition is still within the expected index range, then proceeding to the next process without processing; if the composition deviates, then adjusting the composition, sampling and analyzing again, and performing secondary refining and slag removal until all elements reach the expected index before proceeding to the next process;
[0064] Step (4), after the refining is completed, the melt is allowed to stand for a period of time while maintaining a certain temperature, and then the aluminum alloy liquid is released from the bottom of the furnace for casting, the casting temperature is 712°C, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the amount of aluminum-titanium-boron intermediate alloy added is based on the Ti element content reaching 0.08%. After the aluminum alloy liquid is subjected to a double-stage filtration treatment of 60 mesh and 80 mesh, it enters the casting mold for semi-continuous casting, and the crystallizer descends four degrees at 154 mm / min, and then a round rod-shaped ingot with a diameter of 150 mm is obtained;
[0065] Step (5), placing the round rod ingot into a heating furnace, heating and keeping it at 560° C. for 5 hours for homogenization treatment, then taking the ingot out of the heating furnace and cutting a certain length, and the remaining ingot is again placed in the heating furnace for insulation, and the cut ingot is placed in an extruder and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and the profile extrusion speed is controlled at 6 meters / minute. After the profile is extruded from the extruder outlet, it is immediately subjected to strong wind cooling and spray cooling, and then the profile is straightened and cut into the required length;
[0066] Step (6), placing the extruded profile into an aging furnace for artificial aging treatment, wherein the artificial aging temperature is controlled within the range of 170 to 195° C., and the insulation time is controlled within 3 hours. After the insulation is completed, the profile is taken out of the furnace and cooled to room temperature, and anodized to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0067] Example 5
[0068] A high-strength aluminum alloy material for a photovoltaic panel assembly comprises the following components in mass percentage: Si: 0.60%, Cu: 1.01%, Mg: 0.94%, Mn: 0.70%, Ni: 0.14%, Ag: 0.15%, Ti: 0.07%, B: 0.010%, Sm: 0.15%, Eu: 0.15%, Yb: 0.10%, Fe: 0.15%, other inevitable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum; wherein the mass fraction ratio of Sm, Eu and Yb is 1.8:4.3:2.2.
[0069] The preparation method thereof comprises the following steps:
[0070] Step (1), according to the alloy material components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum manganese master alloy, aluminum titanium boron master alloy, aluminum samarium master alloy, aluminum nickel master alloy, aluminum silver master alloy, aluminum europium master alloy, aluminum ytterbium master alloy raw materials are configured and weighed;
[0071] Step (2), electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy as the first batch of raw materials are loaded into a melting furnace, heated to 755-780°C to melt the charge, and kept warm at 760°C and mechanically stirred; the first batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 725-765°C, a second batch of raw materials such as aluminum silver master alloy, aluminum samarium master alloy, aluminum europium master alloy, and aluminum ytterbium master alloy are added, and the temperature is kept warm at 740°C, and mechanical stirring is maintained during the period; the second batch of charge is completely melted and stirred evenly, and after the furnace temperature drops to the range of 680-720°C, a magnesium ingot is added, and the temperature is kept warm at 730°C, and mechanical stirring is maintained during the period; after stirring evenly, a small amount is taken out from the high-temperature aluminum alloy liquid for chemical composition analysis, if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators;
[0072] Step (3), refining the aluminum alloy melt in the smelting furnace, maintaining the refining temperature in the range of 715-730°C, using 99.99% high-purity argon gas, refining for 60 minutes, then removing the slag produced in the furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, then proceeding to the next process without processing; if the composition deviates, then adjusting the composition, sampling and analyzing again, and performing secondary refining and slag removal until all elements reach the expected index before proceeding to the next process;
[0073] Step (4), after the refining is completed, the melt is allowed to stand for a period of time while maintaining a certain temperature, and then the aluminum alloy liquid is released from the bottom of the furnace for casting, the casting temperature is 712°C, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the amount of aluminum-titanium-boron intermediate alloy added is based on the Ti element content reaching 0.08%. After the aluminum alloy liquid is subjected to a double-stage filtration treatment of 60 mesh and 80 mesh, it enters the casting mold for semi-continuous casting, and the crystallizer descends four degrees at 154 mm / min, and then a round rod-shaped ingot with a diameter of 150 mm is obtained;
[0074] Step (5), placing the round rod ingot into a heating furnace, heating and keeping it at 560° C. for 5 hours for homogenization treatment, then taking the ingot out of the heating furnace and cutting a certain length, and the remaining ingot is again placed in the heating furnace for insulation, and the cut ingot is placed in an extruder and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and the profile extrusion speed is controlled at 6 meters / minute. After the profile is extruded from the extruder outlet, it is immediately subjected to strong wind cooling and spray cooling, and then the profile is straightened and cut into the required length;
[0075] Step (6), placing the extruded profile into an aging furnace for artificial aging treatment, wherein the artificial aging temperature is controlled within the range of 175 to 195° C., and the insulation time is controlled within 3 hours. After the insulation is completed, the profile is taken out of the furnace and cooled to room temperature, and anodized to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
[0076] Comparative Example 1
[0077] The aluminum lamp poles made of 6005 aluminum alloy are used for comparison. The 6005 aluminum alloy is made into corresponding extruded profiles through smelting casting, hot extrusion, solution treatment and artificial aging.
[0078] Comparative Example 2
[0079] The aluminum lamp poles made of 6063 aluminum alloy are used for comparison. The 6063 aluminum alloy is made into corresponding extruded profiles through smelting casting, hot extrusion, solution treatment and artificial aging.
[0080] Performance Testing
[0081] The photovoltaic panel frames and purlins manufactured in Examples 1-5 and the photovoltaic panel frames and purlins manufactured in Comparative Examples 1-2 were tested as follows:
[0082] 1. Room temperature mechanical properties test
[0083] According to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method", random positions of the photovoltaic panel frames and purlins manufactured in Examples 1-5 and the photovoltaic panel frames and purlins prepared in Comparative Examples 1-2 were sampled and machined into tensile specimens, and tested on a tensile testing machine. The results are shown in Table 1.
[0084] Table 1 Test results of mechanical properties of photovoltaic panel frame and purlin materials
[0085] Alloy Material state Yield strength / MPa Tensile strength(MPa) Elongation(%) Example 1 T5 267 331 16 Example 2 T5 286 343 14 Example 3 T5 256 318 13 Example 4 T5 278 380 15 Example 5 T5 260 325 16 6005 Aluminum Alloy T5 196 240 14 6063 Aluminum Alloy T5 180 223 14
[0086] It can be seen from Table 1 that the yield strength, tensile strength and elongation of the photovoltaic panel frame and purlin profiles obtained in Examples 1-5 of the present invention are higher than those of the photovoltaic panel frame and purlin profiles made of 6005 and 6063 aluminum alloys. Therefore, the photovoltaic panel frame and purlin profiles obtained by the present invention have high strength and hardness.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength aluminum alloy material for photovoltaic panel components, characterized in that: The invention comprises the following components in mass percentage: Si: 0.09-0.9%, Ti: 0.009-0.16%, Mg: 0.3-1.3%, Yb: 0.02-0.7%, Mn: 0.5-1.3%, Cu: 0.08-1.3%, Ag: 0.04-0.4%, B: 0.001-0.04%, Sm: 0.02-0.7%, Eu: 0.02-0.7%, Ni: 0.02-0.4%, Fe≤0.4%, other unavoidable single impurity elements≤0.04%, the total amount of impurity elements≤0.16%, and the balance is aluminum.
2. The high-strength aluminum alloy material for photovoltaic panel components according to claim 1, characterized in that: The aluminum alloy material for photovoltaic panel frames and purlins includes the following components in mass percentage: Si: 0.39-0.9%, Cu: 0.39-1.1%, Mg: 0.39-1.1%, Mn: 0.59-1.1%, Ni: 0.04-0.21%, Ag: 0.02-0.21%, Ti: 0.01-0.13%, B: 0.001-0.026%, Sm: 0.02-0.41%, Eu: 0.02-0.41%, Yb: 0.02-0.41%, Fe≤0.31%, other unavoidable single impurity elements≤0.031%, the total amount of impurity elements≤0.151%, and the balance is aluminum.
3. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 1 or 2, characterized in that: The following steps are involved: Step (1), according to the composition of the high-strength aluminum alloy material for photovoltaic panel components, magnesium ingot, electrolytic copper, aluminum ingot, aluminum-manganese master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy raw materials are configured and weighed; Step (2), after placing the first batch of furnace materials: electrolytic copper, aluminum ingot, aluminum nickel master alloy, aluminum manganese master alloy in a smelting furnace, heating the smelting furnace to melt and carry out the first stage of heat preservation smelting, after the furnace materials are melted and reach the expected temperature, mechanical stirring is carried out, and the temperature of the smelting furnace is maintained during stirring; after the first batch of furnace materials are completely melted and stirred evenly, the second batch of furnace materials: aluminum ytterbium master alloy, aluminum samarium master alloy, aluminum europium master alloy, aluminum silver master alloy are added to the smelting furnace, after the furnace materials are completely melted, mechanical stirring is carried out, during stirring, the temperature of the smelting furnace is maintained and the second stage of heat preservation smelting is carried out; after the second batch of furnace materials are completely melted and stirred evenly, magnesium ingot is added, after the magnesium ingot is melted, mechanical stirring is maintained to make the melt uniform, during which the temperature of the smelting furnace is maintained and the third stage of heat preservation smelting is carried out; after stirring evenly, a small amount is taken out from the high-temperature aluminum alloy liquid for chemical composition analysis, if the composition is deviated, the composition is adjusted and sampled again for analysis until all elements reach the expected indicators; Step (3), refining the aluminum alloy melt in the smelting furnace, then removing the slag produced in the smelting furnace, sampling and analyzing again after the refining is completed, and if the composition is still within the expected index range, it does not need to be processed and enters the next process; if the composition deviates, the composition is adjusted, and then sampling and analyzing again, and secondary refining and slag removal are performed, until all elements reach the expected index before entering the next process; Step (4), after the refining is completed, the melt is allowed to stand for a period of time, and the melt is kept at a certain temperature before the aluminum alloy liquid is released from the bottom of the furnace for casting, and when the aluminum alloy liquid enters the flow channel, aluminum-titanium-boron intermediate alloy wire is added thereto for grain refinement treatment, and the aluminum alloy liquid is subjected to double-stage filtration treatment and then enters the casting mold for semi-continuous casting to obtain a round rod-shaped ingot; Step (5), placing the round rod ingot in a heating furnace for heating and heat preservation for a certain period of time, then performing a homogenization treatment, then taking the ingot out of the heating furnace and cutting a certain length, and the remaining ingot is again placed in the heating furnace for heat preservation, and the cut ingot is placed in an extruder, and extruded into a profile of the required size and shape of the photovoltaic panel frame and purlin, and after being extruded from the extruder, it is cooled to room temperature by strong wind, and then the cooled profile is straightened and cut into the required length; Step (6), placing the profile obtained in step (5) into an aging furnace for artificial aging treatment, taking it out of the furnace after the heat preservation is completed, cooling it to room temperature, and performing an anodizing treatment on it to obtain an aluminum alloy material for photovoltaic panel frames and purlins.
4. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (1), the contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.4-10.6%, and the ratio of the addition amounts of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is (1-4):(2-7):(1-4).
5. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (2), the first stage heat preservation and melting temperature is 730-830°C, the second stage heat preservation and melting temperature is 720-790°C, and the third stage heat preservation and melting temperature is 670-750°C.
6. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (3), the refining temperature is 670-750° C., the refining time is 40-100 minutes, and the refining gas is 99.99% high-purity argon.
7. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (4), the casting temperature is 650-740°C; the Ti content in the alloy after the addition of the aluminum-titanium-boron master alloy is 0.01-0.06%; the first stage of the two-stage filtration uses a 55-65 mesh ceramic filter plate, and the second stage uses a 75-85 mesh ceramic filter plate; the crystallizer descent speed is 35-245 mm / min.
8. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (5), the homogenization temperature is 440-610° C., the homogenization time is ≥4.5 hours, the extrusion speed is 1-13 m / min, and the cooling method is a combination of strong air cooling and spray cooling.
9. The method for preparing a high-strength aluminum alloy material for a photovoltaic panel assembly according to claim 3, characterized in that: In step (6), the artificial aging temperature is 140 to 230° C., and the insulation time is 2 to 13 hours.